Foundations for Moral Relativism : Second expanded edition - J. David Velleman
In this new edition of Foundations for Moral Relativism, a distinguished moral philosopher tames a bugbear of current debate about cultural difference. J. David Velleman shows that different communities can indeed be subject to incompatible moralities, because their local mores are rationally binding. At the same time, he explains why the mores of different communities, even when incompatible, are still variations on the same moral themes. The book thus maps out a universe of many moral worlds without, as Velleman puts it, "moral black holes". The six self-standing chapters discuss such diverse topics as online avatars and virtual worlds, lying in Russian and truth-telling in Quechua, the pleasure of solitude and the fear of absurdity. Accessibly written, Foundations for Moral Relativism presupposes no prior training in philosophy.